2020
DOI: 10.1016/j.arthro.2020.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Commentary: The Segond Fracture Has Multiple Attachments: Yet Another Demonstration of the Anatomical Complexity of the Anterolateral Complex of the Knee

Abstract: The anterolateral complex (ALC) of the knee comprises multiple layers, with continued debate on the identity and function of the structures of the ALC. The Segond fracture, long considered pathognomonic of an anterior cruciate ligament injury, has now been shown to have several attachments to soft tissues of the ALC. To the extent that a Segond fracture, or injury to the ALC more broadly, increases knee rotatory instability in vivo is a question of ongoing investigation. By extension, it remains uncertain whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Recently, the Segond fracture has been of particular interest, as this avulsion fracture has been argued to represent an ALC injury of the knee, which remains a hotly debated topic. 7,12,14,19,32,40 Although some studies concurred with this original description, 20,36,40 others reported that a Segond fracture is an avulsion of the ALL. 7,9,11,19 The ALC Consensus Group stated that ''multiple structures, including ALL, deep iliotibial band and biceps aponeurosis, attach in the region of the Segond fracture, and that it remains unclear which may be responsible for this lesion.''…”
Section: Discussionmentioning
confidence: 81%
“…Recently, the Segond fracture has been of particular interest, as this avulsion fracture has been argued to represent an ALC injury of the knee, which remains a hotly debated topic. 7,12,14,19,32,40 Although some studies concurred with this original description, 20,36,40 others reported that a Segond fracture is an avulsion of the ALL. 7,9,11,19 The ALC Consensus Group stated that ''multiple structures, including ALL, deep iliotibial band and biceps aponeurosis, attach in the region of the Segond fracture, and that it remains unclear which may be responsible for this lesion.''…”
Section: Discussionmentioning
confidence: 81%
“…23,24 Segond fractures, while uncommon, are also significant. 8,9 Additional indications include generalized ligamentous hyperlaxity 25 and proven lesions of the anterolateral knee structures. 15 A retrospective review of ACL reconstruction patients with ligamentous hyperlaxity (minimum score of 5 on the modified Beighton scale) found that the addition of an ALL reconstruction to an anatomic ACL reconstruction resulted in lower KT-1000 scores, better pivot shift tests, and lower reconstruction failure rates: 21.7% (ACL group) versus 3.3% (ACL/ALL group); P ¼ .03.…”
mentioning
confidence: 99%